Intra-operative uterine artery embolization with caesarean delivery in an adjoining operating theatre and catheter lab (OT/CL) complex vs. conventional management in patients with abnormally invasive placenta: a retrospective case control study. (2nd April 2020) - Mohan, Bishav; Wander, Gurleen; Bansal, Raahat; Mutti, Jasmine; Tandon, Pooja; Juneja, Sunil; Puri, Suman
Abstract: Patients of abnormally invasive placenta (AIP) undergoing caesarean delivery are at increased risk of haemorrhage. Conventional management includes piecemeal removal of placenta or placenta left in situ . However, they often require hysterectomy after delivery. Post-delivery prophylactic uterine artery embolisation (UAE) can help reduce morbidity and preserve fertility. We created an adjoining operating theatre and catheter lab (OT/CL complex). This is a retrospective case control study in which 37 patients of AIP were evaluated. Sixteen subjects (cases) had UAE immediately after caesarean delivery, and 21 subjects (controls) had usual care with traditional methods of controlling postpartum haemorrhage and hysterectomy where required. The hysterectomy rate (18.7% vs. 85.7%), mean duration of hospital stay (6.8 ± 2.6 vs. 13.9 ± 8.1) and number of units of blood transfusion required were significantly less in the case group as compared with controls. UAE is an effective conservative treatment along with caesarean delivery in patients with AIP. Impact statement: What is already known? AIP is associated with high rates of PPH, maternal morbidity and mortality and need for hysterectomy after delivery. UAE has been advocated to preserve fertility and reduce PPH in these patients along with caesarean delivery. What do es the study add? We created an adjoining operating theatre and catheter lab (OT/CL complex) in a tertiary care centre and managed these patients with prompt UAE after caesarean delivery with team approach. We have shown significant reduction in morbidity and hospital stay with this coordinated management. What are the implications for clinical practice and/or further research? UAE with caesarean delivery is a preferred mode of delivery for patients of AIP. These patients should be diagnosed and referred to tertiary care centres with such facilities electively so as to provide optimal care to these patients. Cooperation between interventionist and obstetrician and adjoining availability of OT and catheter lab can further help in reducing the time to embolisation after delivery. A hybrid operating theatre with digital subtraction angiography (DSA) facilities would be ideal for the management of such patients.